The Insider : How the Kiplinger Newsletter Bridged Washington and Wall Street - Wells, Rob (Book collections on Project MUSE., 2022)
"When Willard M. Kiplinger launched the groundbreaking Kiplinger Washington Letter in 1923, he left the sidelines of traditional journalism to strike out on his own. With a specialized knowledge of finance and close connections to top Washington officials, Kiplinger was uniquely positioned to tell deeper truths about the intersections between government and business. With careful reporting and insider access, he delivered perceptive analysis and forecasts of business, economic, and political news to busy business executives, and the newsletter's readership grew exponentially over the coming decades. More than just a pioneering business journalist, Kiplinger emerged as a quiet but powerful link between the worlds of Presidents Hoover and Roosevelt, and used his Letter to play a little-known but influential role in the New Deal. Part journalism history, part biography, and part democratic chronicle, The Insider offers a well-written and deeply researched portrayal of how Kiplinger not only developed a widely read newsletter that launched a business publishing empire but also how he forged a new role for the journalist as political actor"--